Rancang Bangun Alat Pengering Biji Kopi Menggunakan Pemanas Kompor Gas Lpg Dengan Model Roll - Reza Anjasmara Prasetya, Mochamad Arif Irfa’i, Agung Samudra (Universitas Hasyim Asy'ari, 2020)
Coffee is one of the major agricultural commodities in Indonesia. The drying process is carried out conventionally (naturally), requires a relatively longer drying time between 1-2 weeks depending on the weather and hot sun, to shorten the time in the coffee bean drying process, a replacement heat source is needed, using a dryer with a roll tube type. which rotates using an LPG gas stove heater. The drying process uses drying variations of 60, 120, and 180 minutes with an initial weight of 1000 gr coffee beans with an initial moisture content of 22.8%. The drying process took 60 minutes, the weight of coffee beans was 955 gr, with 21% moisture content, temperature 42 ° C. Time 120 minutes, weight 911 gr with 20% moisture content, temperature 42 ° C, while time 180 minutes, weight yield 863 gr, water content 17%, with a temperature of 43.5 ° C. The greater the temperature in the drying process, the more effective it is to reduce the weight and moisture content of the coffee beans. The standard of coffee beans is 12% with a maximum drying temperature of 55 ° C.